1977
DOI: 10.1111/j.1600-0714.1977.tb01644.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Evidence for Neural Crest Origin of the Melanotic Neuroectodermal Tumor of Infancy

Abstract: A case of melanotic neuroectodermal tumor of infancy, which occurred in the anterior maxilla of a 3-month-old girl, was studied by electron microscopy. Polymorphic cellular elements were revealed to be present: large melanin-producing cells with some of the characteristics of a neuroepithelium, small non-pigmented cells resembling immature neuroblasts, and many intermediate forms resembling differentiating neuroblasts. All cell types clearly demonstrated ultrastructural features of neurogenic cells, e.g. neuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…However, a negative rate of VMA should not influence the diagnosis of MNTI, because not all the cells of the neural crest are involved in the metabolism of catecholamines. The histochemical and ultra structural features of MNTI cells make them very similar to the neural crest cells (9). The large cells with melanin resemble a neuroepithelium, while the small non-pigmented cells resemble immature neuroblasts, or differentiating neuroblasts (10).…”
Section: Etiopathogenic Hypothesesmentioning
confidence: 97%
“…However, a negative rate of VMA should not influence the diagnosis of MNTI, because not all the cells of the neural crest are involved in the metabolism of catecholamines. The histochemical and ultra structural features of MNTI cells make them very similar to the neural crest cells (9). The large cells with melanin resemble a neuroepithelium, while the small non-pigmented cells resemble immature neuroblasts, or differentiating neuroblasts (10).…”
Section: Etiopathogenic Hypothesesmentioning
confidence: 97%
“…Therefore, one would expect other markers for neural tissue, including neurofilaments or glial filaments, the intermediate filament types present in neurons or astrocytes, respectively, to be present in these cells (6)(7)(8). In electron microscopic studies (9), intermediate-sized filaments (10-nm thick) have been reported for melanin-forming neuroectodermal tumor cells and have been referred to as tonofilaments (10) or neurofilaments (11). In general, the type of intermediate-sized filaments present in specific cell types seems to depend primarily on their differentiation and embryological origin (4).…”
Section: Introductionmentioning
confidence: 99%
“…The large polygonal pigmented cells showed desmosomal thickenings in the cell membrane and presence of melanin granules at different stages of maturation in the cytoplasm whereas the non-pigmented cells were small neuroblast-like cells with hyperchromatic nucleus, scanty cytoplasm and neurite-like cytoplasmic processes. 12 Immunohistochemical studies to identify various tissue markers in MNTI were first reported in 1985. Melissari et al 24 confirmed the neural crest origin of MNTI by using NSE, a marker for neuronal and peripheral neuroendocrine cells and neuroendocrine tumours and S100 protein stain found in glial tissue and in Schwann cells.…”
Section: Discussionmentioning
confidence: 99%
“…11 Electron microscopic studies revealed neural, epithelial and melanotic structures with demonstration of neurosecretory granules; fine, delicate cytoplasmic fibres suggestive of neurofibrils; desmosomal attachments to adjacent cells and melanosomes in many of the cuboidal cells. 12 Immunohistochemical studies are of assistance in diagnosing difficult cases. The small darkly staining cells exhibit neuroblast-like differentiation, with strong expression of synaptophysin and neuron-specific enolase (NSE).…”
Section: Introductionmentioning
confidence: 99%